Desenvolvimento e caracterização de biofilmes ativos com extrato de bagaço de oliva - Dalfolo, Alice de Carvalho (2022)
Bioactive compounds have been recognized for their antimicrobial and antioxidant properties, gaining prominence in the food industry to be used as a natural aditive. In this sense, the incorporation of bioactive compounds in edible films in a alternative, allowing the achievement of active packaging that helps in food conservation. The objective on this work was to extract boactive compound from olive pomace by two methods (conventional and ultrasound) and aplly the best extract of each method in the development of a biofilm. For this, a factorial design of 2² was apllied whit triplicate at the central point to optimize the alcohol concentration and the extraction time of the two methods. Phenolic analyzes were performed by the Folin method in the extracts and films and atioxidant activity by the DPPH method in the films and characterization of biofilms. The films were prepared with chitosan and gelatin (50/50v) and they were (control, conventional extraction with 5% extract (FEC 60%) and ultrasonic extraction with 5% extract (FEU 80%). The extract optimized by the conventional method was with 60% alcoholic extraction and presented (462.91mg/g of dry sample) of phenolics and the other was the ultrasound method with 80% alcoholic extraction with (524.00mg/g of sample dry). The films presented, control (115.01 mg/g dry sample), the conventional method whit 60% alcoholic extraction (146.25 mg/g dry sample) and the ultrasound method with 80% alcoholic extraction (179.58 mg/g of dry sample) of phenolics, the antioxidant activity was 2.83%, 64.16% and 78.45%, respectively in the films. Furthermore, the films were obtained through the analysis of mechanical properties, contact angle, water vapor permeability, solubility, color, Fourier transform infrared spectroscopy), opacity and biodegradability. It was found that the films containing the incorporation of olive pomace extract had no interference in their thickness. The opacity of the active biofilms was superior to that of the control and due to the contact angle greater than 65°, characteristic for all films, with hydrophobic characteristics. The active biofilms demonstrated that the incorporation of the extract considerably increased the bioactive and antioxidant. In this way, active biofilms were prepared whit olive pomace, which can be used in food conservation, proving to be a promising research for the area.